2015
DOI: 10.1161/cir.0000000000000245
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility and Disqualification Recommendations for Competitive Athletes With Cardiovascular Abnormalities: Task Force 9: Arrhythmias and Conduction Defects

Abstract: A broad range of variations in heart rates and rhythms, specific cardiac arrhythmias, and atrioventricular (AV) and intraventricular conduction disturbances are observed in athletes. Although most are common among nonathletes as well, the special circumstances and pressures related to athletic performance demand a high level of attention. The distinction between normal variants, often exaggerated by the specific physiology of the conditioned athlete, and arrhythmias that may be symptomatic or life-threatening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(55 citation statements)
references
References 45 publications
0
55
0
Order By: Relevance
“…According to a prespecified study protocol, we reserved CMR in case of frequent, complex, or exercise‐induced arrhythmias, which are a recognized subgroup with high risk of underlying cardiovascular disease 5, 15, 16, 17. In 3 of these athletes, postcontrast CMR sequences allowed identification of LV LGE with a subepicardial/midmyocardial (ie, nonischemic) pattern, which was not associated with wall motion abnormalities detectable by either echocardiography or cine‐CMR because of its segmental distribution confined to the outer layer of LV musculature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a prespecified study protocol, we reserved CMR in case of frequent, complex, or exercise‐induced arrhythmias, which are a recognized subgroup with high risk of underlying cardiovascular disease 5, 15, 16, 17. In 3 of these athletes, postcontrast CMR sequences allowed identification of LV LGE with a subepicardial/midmyocardial (ie, nonischemic) pattern, which was not associated with wall motion abnormalities detectable by either echocardiography or cine‐CMR because of its segmental distribution confined to the outer layer of LV musculature.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies indicating that cardiovascular diseases are more commonly observed in athletes with frequent (>500 PVBs/24 hours), exercise‐induced, or complex VAs, further imaging study by CMR was reserved to athletes fulfilling these arrhythmic criteria, in addition to those with abnormal echocardiographic findings 5, 15, 16, 17. Echocardiography and CMR were also performed in a control group of athletes with no or rare (≤10) isolated PVBs matched with a 1:1 ratio for sex, age class, and type of sport, who volunteered to participate.…”
Section: Methodsmentioning
confidence: 99%
“…These data can guide more informed individualized physician and patient decision making for sports participation for athletes with ICDs and continue to support the recent change in eligibility recommendations. 4 …”
Section: Correspondencementioning
confidence: 99%
“…31,42 This recommendation is being reassessed by the AHA/ACC on the basis of recent data. 50 Furthermore, athletes with ICDs, if they have a history of ventricular flutter or ventricular fibrillation, may only engage in class IA sports after a period of three months without episodes requiring device therapy. 50 When appropriate or inappropriate ICD interventions occur, a six-week period refraining from sports should be considered to assess the effect of changes in ICD programming.…”
Section: Implantable Cardioverter-defibrillator Therapy In Young Athlmentioning
confidence: 99%
“…39 According to the AHA/ACC, in athletes with ICDs, participation in class IA sports is reasonable after a period of three months without episodes of ventricular flutter or ventricular fibrillation requiring device therapy (no information is given about the presence of underlying structural heart disease). 50 In 2003, in a group of 132 ICD recipients with HCM, Begley et al observed that 88% of appropriate ICD discharges occurred during sedentary or mild to moderate activity. 51 In eight patients (12%) shocks were delivered during strenuous competitive sports (50% of these during basketball or soccer games) and all were successful.…”
Section: Implantable Cardioverter-defibrillator Therapy In Young Athlmentioning
confidence: 99%